IN VITRO SUSCEPTIBILITY PATTERN OF EXTENDED SPECTRUM Î’-LACTAMASE PRODUCING GRAM NEGATIVE BACILLI AGAINST TETRACYCLINES - Gill, Maria Mushtaq; Usman, Javaid; Hassan, Afreenish; Kaleem, Fatima; Shaheen, Nasira (Journal of Ayub Medical College Abbottabad, 2015)
Background: Extended Spectrum Î²-lactamases (ESBLs) are emerging as common nosocomial pathogens and important cause of mortality and morbidity, if not treated properly. The need of the hour is to find effective treatment options for dealing with ESBL producing organisms. This study was aimed to evaluate in vitro susceptibility pattern of extended spectrum Î²-lactamase producers against tetracyclines. Methods: This descriptive cross-sectional study was carried out in the department of Microbiology, Army Medical College, Rawalpindi, National University of Sciences and Technology over a period of 6 months. Seventy eight non-duplicate isolates were included in the study. ESBL detection was done using Jarlier et al method. In vitro susceptibility of tetracyclines like tetracycline, doxycycline, minocycline and tigecycline was then tested using Modified Kirby Bauer disc diffusion method. The zones of inhibition were measured after completion of incubation period and interpreted as per CLSI and FDA guidelines. Results: Approximately 56.4% of the isolates were Escherichia coli, 28.2% were Klebsiella pneumoniae, 10.26% were Enterobacter species, and 2.6% were each Klebsiella oxytoca and Acinetobacter species. ESBLs were found to be most sensitive to tigecycline, intermediate in susceptibility to minocycline while least sensitive to doxycycline and tetracycline. Conclusion: Among tetracyclines, tigecycline has best in vitro susceptibility against ESBL producing Gram negative rods.